Pembuatan Limbah Kertas Menjadi Seed Paper dalam Pembibitan Tanaman - Fauziah Aliy Ash Shidiq; Lutfiah Ananda; Patricia Shyely Yolanda Manik; Yuyun Yuniar Rohmatin (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
The continuous increase in paper consumption has a direct impact on waste accumulation and environmental degradation due to the exploitation of wood as the primary raw material. This study aims to design an innovative product called seed paper as a solution for managing paper and cardboard waste, transforming it into something more useful while supporting Sustainable Development Goal (SDG) No. 12 on responsible consumption and production. The production method involves several stages: processing waste into pulp, mixing it with chili seeds, followed by natural printing and drying. The analysis shows that both paper and cardboard waste can be processed into an effective planting medium, where the paper naturally decomposes and the embedded seeds germinate once planted. In terms of production costs, one batch of seed paper requires approximately Rp23.000 for the paper variant and cardboard variant. Technically, this process demonstrates that waste, which would otherwise accumulate in landfills, can be transformed into an innovative product that promotes reforestation while also carrying economic value through a structured calculation of the cost of goods sold.